Best Answer

2x times y is written 2xy. This means all three of these numbers multiplied together.

Q: What is 2x X y?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

The result of the equation x + 2y - 2x - y equals x simplifies to y - x.

-3

I presume you mean given y find x: Make x the subject: y = 2x + 3 => 2x + 3 = y => 2x = y - 3 => x = (y - 3)/2 which can also be expressed as: x = 0.5 y - 1.5

y = f(x) = (2x + 1)/(x - 1)y*(x - 1) = (2x + 1) xy - y = 2x + 1xy - 2x = y + 1x(y - 2) = y + 1so x = (y + 1)/(y - 2) assuming yâ‰?2.So the inverse function is f-1(x) = (x + 1)/(x - 2)

If you mean: (2x-7y)(x+y) then it is 2x squared -5xy -7y squared

Related questions

4

The result of the equation x + 2y - 2x - y equals x simplifies to y - x.

-4

2x + 4 = y ...............2x + 4 = y ....................2x + 4 = y .............2*(-6)+ 4 = y x - y = 2 .......<=> ...x - 2x - 4 = 2 .....<=> ...x = -6......... <=>.... x = -6 ..............<=> y = - 8 x = - 6

If: y = x+6 and y = 2x Then: x+6 = 2x And: 6 = 2x-x => 6 = x So: x = 6 and y = 12

y=2x-3 y=-x-3

X + ( 2Y - 2X - Y ) is equal to Y - X

-3

y=f(x)= x(2x+y)=7 f(x)=2x^2 +xy -7 = 0 y=2x^2 +xy -7 y-xy -7 + 2x^2 = 0 y(1-x)=2x^2-7 y=(2x^2-7) / (1-x) Excuse the working. Y equals 2 X squared minus 7 all divided by 1-X

I presume you mean given y find x: Make x the subject: y = 2x + 3 => 2x + 3 = y => 2x = y - 3 => x = (y - 3)/2 which can also be expressed as: x = 0.5 y - 1.5

y=2x-4 y=2x-5 y=1 1=2x-4 -2x = -5 x=2/5 the solution is (x,y) = (2/5,1)

2x = y + 7 x - 2 = y substitute the y from the second equation into the first: 2x = x - 2 + 7 2x = x+5 x = 5 --> y = 5 - 2 y = 3